Investigation of Critical Raw Materials in Sludge of Municipal Wastewater Treatment Plant - Topal, Murat; Topal, E. Isil Arslan (Springer Heidelberg, 2023)
In the present research, lanthanum, vanadium, tungsten, scandium, bismuth, antimony, gallium, phosphorus, magnesium, and cobalt from critical raw materials (CRMs) were monitored for one year in the sewage sludges from an advanced biological wastewater treatment plant with the aim of presentation of possibility of using sewage sludge as a secondary source of critical raw materials. The amounts of the critical raw materials in sewage sludge were calculated annually, and economic values were revealed. Maximum concentrations of lanthanum, scandium, tungsten, bismuth, antimony, gallium, vanadium, cobalt, magnesium, and phosphorus were 4.3, 1.6, 0.5, 1.51, 1.27, 1.7, 23, 5.6, 6500, and 16,170 mg/kg, respectively. In the sewage sludge, the amount of CRMs, which have been formed annually, have been listed as tungsten < scandium < antimony < bismuth < gallium < lanthanum < cobalt < vanadium < magnesium < phosphorus. In autumn, summer, spring, and summer season, the mean highest concentration was for P, while the minimum concentration was for W. In sewage sludge, P and W elements were the highest and the least of the CRMs, respectively. With the recovery of CRMs in sewage sludge, the highest theoric achievable income is for Mg, while the lowest income is for Sb. It is determined that a total of 26,083.8 USD/year could be obtained by recovering the CRMs mentioned here from the sewage sludge.
Keywords: Critical raw material; Treatment; Sludge; Recovery; Monitoring